Analisis Kesejahteraan Cleaning Service pada Perguruan Kristen Methodist Indonesia-1 Medan (PKMI-1) - Nikson I Purba; Mia Aulina Lubis; Malida Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
The welfare of the cleaning service in this study aims to find out and analyze the welfare of the cleaning service at the Indonesian Methodist Christian College-1 Medan (PKMI-1). The method used in this research is qualitative descriptive. The data sources used are primary data and secondary data with a total of 8 informants. The key informant in this research is the person in charge of the cleaning service, the main informant is the cleaning service and the additional informants are the family of the cleaning service. The data collection technique used in this research is observation, interviews and documentation. The theory used to analyze the problem in this research is the theory of the Central Statistics Agency (BPS) regarding Indicators of People's Welfare in 2022. According to the Central Statistics Agency (BPS) there are five indicators to determine the level of People's Welfare, namely: Health, Education, Employment, Level and Consumption Patterns, Housing and the Environment. The results of this research show that: The majority of cleaning service families belong to prosperous category I with 2 informants, 3 informants belonging to prosperous family category II, and 2 informants belonging to prosperous family category III. This shows that the condition of cleaning service families working at the Indonesian Methodist Christian College-1 Medan (PKMI-1) is that there are still poor families, namely Jesika's mother's family and other families are no longer included in the poor category.